Formulating an Effectiveness and Transparency Based Village Governance Model as a Continuation of Village Government Transformation - Safitri, Nursan; Nurinda, Nurinda; Asrandi, Asrandi (LPPM Universitas Jambi, 2026)
Village governance requires an integrated governance model to strengthen the quality of public administration and ensure sustainable rural development. This study aims to formulate an Integrative Village Governance Model Based on Effectiveness and Transparency that can enhance the performance and accountability of village governance. A qualitative exploratory approach was employed through in-depth interviews with 12 key informants, supported by document analysis and Reflexive Thematic Analysis to identify the core dimensions shaping effective village governance. The findings indicate that transparency serves as the foundation for building public trust, encouraging community participation, strengthening social oversight, improving accountability, and enhancing governance effectiveness. These governance outcomes are reinforced by several supporting factors, including human resource capacity, leadership, institutional coordination, regulatory support, adequate funding, infrastructure, and digitalization. Based on these findings, the study proposes an Integrative Village Governance Model that systematically links these dimensions to improve governance performance. The model contributes to the development of village governance theory by integrating effectiveness and transparency into a comprehensive governance framework. Practically, it provides guidance for village governments and policymakers in designing governance strategies that are more transparent, participatory, accountable, and sustainable